Agronomic performance and consumer acceptability of improved water yam (Dioscorea alata L.) varieties in the Republic of Benin - Dansi, M.; Loko, Y.L.E.; Fakorede, J.G.; Agre, A.P.; Laly, J.; Amegan, A.; Ogou, H.; Adebola, P.O.; Yedomonhan, H.; Dansi, A.A. (Elsevier, 2024)
White yam (Dioscorea rotundata L.) is widely cultivated, and is a staple food in the Republic of Benin. However, its production is highly sensitive to soil infertility, leading to low yields over the years. In order to address the challenges of land reduction and climate change, it is crucial to introduce more adapted yam varieties to traditional Beninese agriculture. Water yam (Dioscorea alata L.) varieties are viable options, as they need less soil fertility and yield more than D. rotundata, but have a poor culinary performance. The aim of this study is to assess the agronomic and culinary performance of 15 improved water yam genotypes developed by the International Institute of Tropical Agriculture (IITA) compared to local cultivars. In 2022 and 2023, multilocal trials (4 sites) were performed in the yam-growing areas, and nine villages were selected for culinary evaluation. Linear mixed-effects models and generalized mixed-effects models showed significant differences (p < 0.05) in location, year of experimentation, and certain evaluated agronomic parameters. The improved varieties had a strong likelihood of producing small tubers that could be used as seeds. The agronomic and culinary performance of local water yam accessions has been superior to that of improved varieties. Due to its numerous medium tubers, TDa_1508044 could be introduced for production of yam chips. TDa_1510080, which showed a stable high yield throughout the trial sites, and TDa_1510119, which gave a great number of marketable large-size tubers, showed the best agronomic performance with a yield of more than 25 t/ha. TDa_1510043, TDa_0000194, and TDa_1515030 improved varieties that performed well in both culinary and agronomic ways could be widely adopted by farmers in the yam-growing areas of Benin.